RESEARCH NON-LINEARY DEMAND FUNCTION AND EQUILIBRIUM INDICATORS OF SUPPLY CHAIN UNDER ІNFORMATION ASYMMETRY BY THE MEANS OF THE PACKAGE SYMBOLIC TRANSFORMATION MAPLE - V. М. Kobets (Kherson State University, 2011)
In the paper is investigated the research issues of nonlinear economical indicators for market structures by means of the symbol transformation system Maple.